DELVING INTO PRE-SERVICE ELEMENTARY SCHOOL TEACHERS’ ATTITUDES, PERCEIVED USEFULNESS AND KNOWLEDGE OF UTILISING USER-GENERATED MICROGAMES FOR TEACHING - Sasih Karnita Arafatun; Imam Fitri Rahmadi (UNMUHBABEL Press, 2024)
User-generated microgames, as very small games created by individual users or communities, have garnered great attention in educational research for their potential to enhance learning experiences. To the best of our knowledge, how preservice teachers’ responses, beliefs and knowledge about these microgames are still not completely understood. The present study attempts to understand pre-service elementary school teachers’ attitudes, perceived usefulness and knowledge of utilising user-generated microgames for teaching. A descriptive cross-sectional study was conducted with the participation of 150 pre-service elementary school teachers from three different teacher education universities located in Jakarta, Kudus, and Pangkalpinang, Indonesia. The results indicate that teachers generally hold positive attitudes toward using user-generated microgames in teaching and recognise their usefulness as instructional tools for enhancing engagement and teaching quality. They demonstrate confidence in their technological pedagogical content knowledge (TPACK), particularly in selecting and implementing these microgames and addressing diverse learning modalities. However, variability in overall responses and a lower confidence in extracting essential information from the games highlight areas requiring further professional development in future endeavours.